Suppressive subtractive hybridization reveals different gene expression between high and low virulence strains of Cladosporium cladosporioides. (November 2016) - Gu, Yu; Liu, Yanfang; Cao, Sanjie; Huang, Xiaobo; Zuo, Zhicai; Yu, Shumin; Deng, Junliang; Ding, Chunbang; Yuan, Ming; Shen, Liuhong; Wu, Rui; Wen, Yiping; et al.
Abstract: Cladosporium cladosporioides is a ubiquitous fungus, causing infections in plants, humans, and animals. Suppression subtractive hybridization (SSH) and quantitative real-time PCR (qRT-PCR) were used in this study to identify differences in gene expression between two C . cladosporioides strains, the highly virulent Z20 strain and the lowly virulent Zt strain. A total of 61 unigenes from the forward library and 42 from the reverse library were identified. Gene ontology (GO) analysis showed that these genes were involved in various biological processes, cellular components and molecular functions. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that the unigenes in the forward library corresponded to 5 different pathways and the reverse library unigenes were involved in 3 different pathways. The qRT-PCR results indicated that expressions of APL1, GUD1, CSE1, SPBC3E7 . 04c and MFS were significantly different between Z20 and Zt strains, while genes encoding the senescence-associated proteins, pse1, nup107, mip1, pex2, icl1 and α/β hydrolase exhibited no significant differences between the two strains. In addition, we found that 5 unigenes encoding mip1, chk1, icl1, α/β hydrolase and β-glucosidase may be associated with pathogenicity. One unigene ( MFS ) may be related to the resistance to 14 α-demethylase inhibitor fungicides, and 5 unigenes ( PEX2, NUP107, PSE1, APL1, and SPBC3E7 . 04c ) may be related to either low spore yield or earlier aging of the Zt strain. Our study may help better understand the molecular mechanism of C . cladosporioides infection, and therefore improve the treatment and prevention of C . cladosporioides induced diseases. Highlights: Roughly understand the molecular mechanism of Cladosporium cladosporioides infection. Found 5 unigenes may associated with pathogenicity in C . cladosporioides . Found C . cladosporioides have resistance to 14 α-demethylase inhibitor fungicides. 5 unigenes related to either low spore yield or earlier aging in C . cladosporioides .